Factors Analysis That Affecting The Treatment Success In Tb Patients In Situbondo Regency - Sasmita, Hasri Yulia; Peristiowati, Yuly; Nurwijayanti (Indonesian Journal of Tropical and Infectious Disease, 2025)
Tuberculosis (TB) remains one of the top 10 lethal infectious diseases). In addition, the low case detection rate indicates that the community still has a large number of sources of transmission. Directly Observed Treatment Short-course (DOTS) strategy aims to reduce the new TB cases number by 80% and deaths by up to 90% in 2030. Drug-resistant TB cases especially multidrug resistant TB, exacerbate tuberculosis control because they receive TB treatment irregularly and do not comply to recommended treatment schedules, nonetheless, consistent treatment is critical to successful TB treatment. TB data in Situbondo district show that case detection was 911 out of 1539 cases or 59.14% and treatment success rate was 275 out of 911 cases or 30.2%. This study aims to examine the influence of knowledge, medication supervisors, family support, drug side effects, attitudes, length of treatment, and house physical environment on the treatment success through medication compliance factors. This research is explanatory with 196 respondents while the analysis uses SMART PLS 4.1.0.3. There is a direct influence of medication supervisors, family support, drug side effects, house physical environment and medication compliance and an indirect influence of medication supervisors, family support, drug side effects, and attitudes to TB treatment success. It is hoped that Public Health Centre officers can be more active to educate, detect TB suspect, and also supervise patient so compliance and treatment can be achieved. The patient's family can be more active in providing support during the treatment period for TB sufferers.